2020
DOI: 10.3390/ijms21197172
|View full text |Cite
|
Sign up to set email alerts
|

Iris Colour and the Risk of Developing Uveal Melanoma

Abstract: Uveal melanoma (UM) is a global disease which especially occurs in elderly people. Its incidence varies widely between populations, with the highest incidence among Caucasians, and a South-to-North increase in Europe. As northern Europeans often have blond hair and light eyes, we wondered whether iris colour may be a predisposing factor for UM and if so, why. We compared the distribution of iris colour between Dutch UM patients and healthy Dutch controls, using data from the Rotterdam Study (RS), and reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 131 publications
3
29
0
2
Order By: Relevance
“…The quality and quantity of melanin determines the extent of susceptibility to UVR damage in melanocytes and this correlates with UM risk. Having light (blue, gray, green or hazel) coloured eyes as opposed to dark (brown or black) coloured eyes has frequently been found to be a mild to major risk factor for developing UM (see Table 1 ) in Australia [ 33 , 34 ] and countries in the northern hemisphere [ 30 , 32 , 35 ]. This could be due to the UVR protective properties of eumelanin in darker eye colours [ 5 ].…”
Section: Interactions Between Uvr and The Eyementioning
confidence: 99%
See 1 more Smart Citation
“…The quality and quantity of melanin determines the extent of susceptibility to UVR damage in melanocytes and this correlates with UM risk. Having light (blue, gray, green or hazel) coloured eyes as opposed to dark (brown or black) coloured eyes has frequently been found to be a mild to major risk factor for developing UM (see Table 1 ) in Australia [ 33 , 34 ] and countries in the northern hemisphere [ 30 , 32 , 35 ]. This could be due to the UVR protective properties of eumelanin in darker eye colours [ 5 ].…”
Section: Interactions Between Uvr and The Eyementioning
confidence: 99%
“…This was repeated in a study investigating 16 European countries (6673 patients from 1983 to 1994), where incidence rates increased, rather than decreased, with latitudes further away from the equator [ 25 ]. This could be attributed to a higher proportion of light-coloured eyes in northern Europe [ 25 , 35 ]. However, an analysis of 2142 ocular melanomas from 1992–2002 in the US, which focused on non-Hispanic whites, revealed a significant increase (4.91- fold) in UM incidence with increasing latitudes (20–22° to 47–48°) [ 94 ].…”
Section: Uvr Susceptibility Relating To Environmental Factorsmentioning
confidence: 99%
“…Although several studies from Canada, the United States, Germany, France, the Netherlands, and Australia have shown that UM is more prevalent in people with lighter iris color ( Gallagher et al, 1985 ; Holly et al, 1990 ; Seddon et al, 1990 ; Pane and Hirst, 2000 ; Guénel et al, 2001 ; Stang et al, 2003 ; Schmidt-Pokrzywniak et al, 2009 ; Houtzagers et al, 2020 ), the proportion of patients with brown eyes in these studies is very low. Therefore, the relationship between iris color and the incidence of UM in the Asian population requires a closer examination.…”
Section: Introductionmentioning
confidence: 90%
“…Lack of pigmentation leads to more light penetration into the uvea and less protection from ultraviolet radiation (UV), which increases the risk of UM ( Egan et al, 1988 ; Singh and Topham, 2003 ). It has also been suggested ( Houtzagers et al, 2020 ) that most UV rays are absorbed by the cornea, lens, and vitreous, while other wavelengths, such as visible light, penetrate the back of the eye and contribute to the production of toxic reactive oxygen species (ROS), thereby increasing the chance of malignant transformation of uveal melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of UM is associated with several individuals’ backgrounds, including race, age, iris color, etc. 1 , 2 For example, it is more prevalent in Caucasians with light irises than brown eyes. The annual incidence in European and American people is approximately 3.75–5.2 cases per million persons, 3 , 4 which is significantly higher than that in Asians and Africans.…”
Section: Introductionmentioning
confidence: 99%